Geologi dan Rezim Tektonik terhadap Evolusi Lengan Utara Sulawesi: Studi Kasus Sungai Alo, Gorontalo - Naafi' Syahna Firdhaus Biya; Aang Panji Permana; Muhammad Kasim (Universitas Negeri Gorontalo, 2025)
This study investigates the tectonic control on the development of geological structures along the Alo River in Tibawa District, Gorontalo Regency, Gorontalo Province. The research was conducted through geological mapping, structural analysis, and petrographic examination of basalt rock samples. The area is characterized by two major geomorphological units: structural hills and floodplains. Stratigraphically, it comprises basalt units—correlated with the Bilungala Volcanic Formation—and alluvial deposits. Structural analysis reveals two orders of joint structures with dominant orientations of NW–SE and N–S, interpreted as the result of multiple tectonic episodes. Petrographic analysis shows porphyritic and intergranular textures with plagioclase, pyroxene, and minor olivine as dominant minerals. Tectonic stress analysis using Win_Tensor software indicates transtensional regimes characterized by normal faulting and strike-slip faults with extensional components. These structures are associated with tectonic evolution in the North Arm of Sulawesi, transitioning from compressional to oblique-extensional settings during the Late Miocene–Pliocene due to changes in subduction geometry and microblock interactions. This ongoing tectonic activity has implications for regional geological mapping and natural resource management in Gorontalo.